2018
DOI: 10.1158/1078-0432.ccr-17-3236
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Discovery and Identification of a Novel miRNA Signature for Recurrence Prediction in Stage II and III Colorectal Cancer

Abstract: The current tumor-node-metastasis (TNM) staging system is inadequate at identifying patients with high-risk colorectal cancer. Using a systematic and comprehensive biomarker discovery and validation approach, we aimed to identify an miRNA recurrence classifier (MRC) that can improve upon the current TNM staging as well as is superior to currently offered molecular assays. Three independent genome-wide miRNA expression profiling datasets were used for biomarker discovery ( = 158) and validation ( = 109 and = 40… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…A number of miRNAs have been detected to predict the survival of patients with CRC (Balaguer et al, 2011;Zhang et al, 2013;Hur et al, 2015;Vychytilova-Faltejskova et al, 2016;Pettit et al, 2017;Toiyama et al, 2017;Ji et al, 2018;Kandimalla et al, 2018). Particularly,, and miR-92a have proven to be correlated with the prognosis or therapeutic outcome of patients with CRC (Gaedcke et al, 2012;Kuo et al, 2012;Schee et al, 2012;Tsai et al, 2013;Yong et al, 2013;Kim et al, 2014;Pichler et al, 2014;Sun et al, 2014;Xue et al, 2014;Fu et al, 2018;Igder et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of miRNAs have been detected to predict the survival of patients with CRC (Balaguer et al, 2011;Zhang et al, 2013;Hur et al, 2015;Vychytilova-Faltejskova et al, 2016;Pettit et al, 2017;Toiyama et al, 2017;Ji et al, 2018;Kandimalla et al, 2018). Particularly,, and miR-92a have proven to be correlated with the prognosis or therapeutic outcome of patients with CRC (Gaedcke et al, 2012;Kuo et al, 2012;Schee et al, 2012;Tsai et al, 2013;Yong et al, 2013;Kim et al, 2014;Pichler et al, 2014;Sun et al, 2014;Xue et al, 2014;Fu et al, 2018;Igder et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) have been developed as novel biomarkers for early non-invasive or minimally invasive diagnosis of CRC (Gangadhar and Schilsky, 2010;Chen et al, 2015). Expression profiles of miRNAs in human colon cancer were utilized to determine the potential clinical relevance in several studies (Smits et al, 2011;Ma et al, 2012;Manceau et al, 2014;Wu et al, 2014;Kandimalla et al, 2018). A single model incorporating multiple biomarkers demonstrates improved performance and stability of prognostic value (Agesen et al, 2012;Marisa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…See related article by Kandimalla et al,p. 3867 In this issue of Clinical Cancer Research, Kandimalla and colleagues present an 8-miRNA signature, validated in independent clinical cohorts, that reliably identifies stage II/III colon cancer patients' risk of relapse (1). This novel recurrence classifier, obtained from formalin-fixed paraffin-embedded specimens, outperformed some widely used prognostic clinicopathologic features and consensus molecular subtypes (CMS).…”
Section: Aacrmentioning
confidence: 99%
“…More recently, data generated from different genomic platforms have defined several molecular subtypes with clinical relevance in stage III colon cancer, such as the poor prognosis CMS4/CDX2 subset or the differential benefit from oxaliplatin between enterocyte and stem-like subtypes. However, as suggested by Kandimalla and colleagues (1), clinical translation of a gene expression panel-based approach may be challenging. Diverse clinical cohorts, different sources from clinical sample acquisition, stromal-derived intratumoral heterogeneity, experimental methodologic differences, different data processing algorithms, inaccuracy to reliably classify patient subtype from biopsy tissue, and spatial and temporal heterogeneity within primary tumor tissue remain major obstacles to its wide implementation.…”
Section: Aacrmentioning
confidence: 99%
“…The Cancer Genome Atlas (TCGA) provides a foundation for systematic analysis of large-scale miRNA expression data. Most recently, a comprehensive study based on the TCGA and other data platforms has successfully identified an 8-miRNA signature that significantly predicted recurrence-free interval in stage II and III colorectal cancer (Kandimalla et al, 2018). In the present study, we employed a large cohort of GC patients from the TCGA project and identified a novel miRNA-based signature for predicting recurrence-free survival (RFS) in patients with GC, followed by validation of its clinical significance in an independent clinical cohort.…”
Section: Introductionmentioning
confidence: 99%